An economic analysis of agrophotovoltaics: Opportunities, risks and strategies towards a more efficient land use - Maximillian Trommsdorff (University of Freiburg, Institute for Economic Research, Department of Economic Policy and Constitutional Economic Theory, 2016)
[Introduction] The way we produce food and generate energy substantially matters for major challenges of this century. Agricultural practices affect biodiversity, human health and quality of water; fossil-fuel power stations drive Carbon Dioxide (CO2) emissions exacerbating global warming; and efficiency of both sectors co-determines how many people do have access to food and energy supply. Seen in this light, it seems plausible that both sectors are - at least in most industrial countries - widely regulated (see e.g. Sumner, Alston, and Glauber, 2010; Pearce, 2002). Indeed, externalities, public good characteristics, spillovers, and issues of just distribution are frequently cited to justify regulations. In such an environment and given rapid changes and developments of today's energy and food branches, it is an indispensable task of efficient governance to constantly monitor and assess technological innovations, either with respect to their eligibility to get supported or with respect to needs of restriction or prohibition. Recent examples of such a process entered the public debate under the headings of genetically modified crops, promotion of Renewable Energies (RE) or hydraulic fracturing. [...]
Keywords: 330